Advances in Fractional Differential Operators and Their Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The application of generalized and fractional derivatives, such as Caputo and Riemann–Liouville derivatives, has witnessed a dramatic increase in recent years. This reprint focuses on related theoretical and applied research in areas such as the stability of time series, Lotka–Volterra systems, distributed delays, Fornberg–Whitham equations, abstract evolution and fractional wave equations, cantilever beams, and fractional Riccati and Volterra equations, as well as fractional visco-elasto-plasticity, spectral theory for fractional Sturm–Liouville problems, generalized differential equations, Mittag–Leffler functions, and fractional Laplacians.